Effects of the Sex Ratio and Socioeconomic Deprivation on Male Mortality. Issue 3 (2nd July 2020) - Moore, F. R.; Macleod, M.; Starkey, C.; Krams, I.; Roy, T.
Abstract : We explored relationships between male mortality and the sex ratio. (We tested relationships across 142 societies and in longitudinal data from Scotland. A male-biased sex ratio was associated with reduced mortality by intentional self-harm across 142 societies. This was replicated in longitudinal Scottish data, and men were less likely to die by suicide and assault when there were more men in the population only when levels of unemployment were low. We argue that this is consistent with a theoretical model in which men increase investment in relationships and offspring as "competition" under a male-biased sex ratio, and that the conflicting results of previous work may stem from divergent effects of the sex ratio on mortality depending upon relative deprivation.